2021
DOI: 10.3390/ijerph18084342
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reduced Training Activity of Elite Kickboxers on Physical Fitness, Body Build, and Performance during Competitions

Abstract: Background: Kickboxing is a combat sport where athletes require constant supervision of a coach. The outbreak of the pandemic caused by SARS-CoV-2 has led to a crisis in many sectors, including sport. Global efforts to limit the spread of the pathogen resulted in temporary lockdowns that limited sporting activity, thus deteriorating athletes’ physical fitness. Methods: The participants included 20 kickboxers competing at the international level. Their physical fitness was evaluated based on the test developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 38 publications
(27 reference statements)
3
47
0
4
Order By: Relevance
“…The indicators also allow for the identification of certain gaps in training. In this study, the level of the indicators of technical and tactical skills was at a high level compared with recent studies conducted by Ambrozy et al (2021). All indicators were well above the average compared with the highest competitive disposition presented by the authors.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…The indicators also allow for the identification of certain gaps in training. In this study, the level of the indicators of technical and tactical skills was at a high level compared with recent studies conducted by Ambrozy et al (2021). All indicators were well above the average compared with the highest competitive disposition presented by the authors.…”
Section: Discussionsupporting
confidence: 41%
“…Three parameters (i.e., the efficiency of the attack, the effectiveness of the attack, and the activeness of the attack) were used to assess the bouts. The level of activeness is measured by the number of techniques used (Ambrozy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…After the removal of duplicated papers (48), studies were left for verification. The final inclusion criterion for the review was met by 14 articles [16,[24][25][26][27][28][29][30][31][32][33][34][35][36]. Details were presented in the PRISMA diagram [19] (Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…The female group (n = 2742) represented the majority of subjects (51%), while the male group (n = 2692) represented a total of 49%. The athletes' age was included in 13 articles [16,[24][25][26][27][28][30][31][32][33][34][35][36]. Only seven studies [16,[25][26][27][28]30,32] included a comparison of the results obtained in times before and during the pandemic, while only one research article [30] characterized the results in relation to the different phases of the pandemic.…”
Section: Search Resultsmentioning
confidence: 99%
“…Most studies have reported an overall decrease in exercise engagement during the pandemic (e.g., [ 8 ]). Some researchers have warned that the forced stop period might result in detraining, related physiological training losses [ 9 ], and negative psychological effects [ 10 , 11 , 12 , 13 , 14 ], particularly among highly active individuals who are known to experience severe deteriorations of well-being in response to exercise deprivation [ 15 , 16 ]. However, more detailed observations show that often, a significant proportion of the samples was able to maintain or even increase their exercise engagement during the current pandemic [ 12 , 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%